2007
DOI: 10.1080/09595230701499191
|View full text |Cite
|
Sign up to set email alerts
|

Changing the density of alcohol outlets to reduce alcohol‐related problems

Abstract: Increasingly, it seems, legal and political debates regarding the granting of new liquor licences are turning to the issue of whether the number and density of alcohol outlets makes a difference in rates of alcohol consumption and alcohol-related harm. But what is the state of the evidence on this question? In this Harm Reduction Digest Livingston, Chikritzhs and Room review the research literature on the effects of density of alcohol sales outlets on alcohol consumption and alcohol-related problems; suggest a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
216
1
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(226 citation statements)
references
References 58 publications
6
216
1
3
Order By: Relevance
“…(Livingston et al 2007) 230 The clearest evidence of a relationship comes from natural experiments in countries where large-scale policy changes have been implemented over a relatively short time period. Two recent studies from Canada assessed the impact of privatisation of government-run liquor stores on consumption and harm following a 33.4% increase in the number of private liquor stores in British Columbia between 2003 and 2008.…”
Section: Competing Tensions In Shaping Public Health Interventionsmentioning
confidence: 99%
“…(Livingston et al 2007) 230 The clearest evidence of a relationship comes from natural experiments in countries where large-scale policy changes have been implemented over a relatively short time period. Two recent studies from Canada assessed the impact of privatisation of government-run liquor stores on consumption and harm following a 33.4% increase in the number of private liquor stores in British Columbia between 2003 and 2008.…”
Section: Competing Tensions In Shaping Public Health Interventionsmentioning
confidence: 99%
“…The first might be through a correlation with number of shops selling alcohol which is in turn correlated with wellbeing through its effects on violence. A review on the spatial relationship between outlet density and rates of violence found that most studies reported a significant positive relationship (Livingston, et al, 2007), while another study found the density of off-premise alcohol outlets to be related to the rate of alcohol use disorders (Livingston, 2011). Finally, a review of forty-four studies linked density of alcohol outlets to damage from alcohol, with damage defined to include both trauma (intentional and unintentional causes) but also social problems (Popova, Giesbrecht, Bekmuradov, & Patra, 2009).…”
Section: Instrument Exogeneitymentioning
confidence: 99%
“…Reducing access to alcohol through restricting outlet density in communities, blocking access altogether in specific locations (as in some Aboriginal communities) or to certain age groups (Livingston et al 2007;Hogan et al 2006). …”
Section: Community and Population Approaches To Alcohol Problemsmentioning
confidence: 99%